BODY MASS INDEX AND ITS RELATIONSHIP TO PERFORMANCE IN THE SNATCH LIFT AMONG FEMALE WEIGHTLIFTERS OF THE IRAQI NATIONAL WEIGHTLIFTING TEAM - Assistant Professor Saud Abdulghani Majeed Karim; Assistant Professor Ayham Shabib Saleh (Proximus Journal Publishing, 2025)
Interest in different physical capacities and health variables on sports performance has increased due to its importance of improving or diminishing athlete's performances. Body fitness of an athlete: Body fitness of an athlete’s represents a person's encounter and proficiency in using a part or whole body for expressing sensation, performing motion, creating, or transforming physical activity. This extends to many physical and motor abilities. The Body Mass Index (BMI) is a well-established measure of body composition that derives the ratio 'height in cm/weight in kg' for an individual to express its body mass. It may be used as a convenient and useful tool for sports and health professionals in assessing weight status of individuals, along with associated health consequences or risks by looking at the relative risk of diseases compared to normal weight ranges.
Keywords: Body Mass Index; Performance; Snatch Lift